2020
DOI: 10.1038/s41467-020-16316-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-natural ruthenium isotope ratios of the undeclared 2017 atmospheric release consistent with civilian nuclear activities

Abstract: Understanding the circumstances of the undeclared 2017 nuclear release of ruthenium that led to widespread detections of the radioisotope 106 Ru in the Eurasian region, and whether it derives from a civilian or military source, is of major importance for society and future improvements in nuclear safety. Until now, the released nuclear material has merely been studied by analyzing short-lived radioisotopes. Here, we report precise measurements of the stable isotopic composition of ruthenium captured in air fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…30 Stable isotopic anomalies have also been observed on various occasions where a nuclear release impacted the natural isotopic occurrences. 31,32 For cesium isotopes, only the complementary pattern of this isotopic fractionation had been observed previously: 33 in environmental samples taken from more remote locations downwind from the test site, the 135 Cs-rich "far-end" with samples exhibiting a high 135 Cs/ 137 Cs ratio. 33 Here, to the best of our knowledge, we observe for the first time the complementary 137 Cs-rich "near-end" showing the opposite pattern with a low 135 Cs/ 137 Cs signature.…”
Section: Cs Csmentioning
confidence: 73%
“…30 Stable isotopic anomalies have also been observed on various occasions where a nuclear release impacted the natural isotopic occurrences. 31,32 For cesium isotopes, only the complementary pattern of this isotopic fractionation had been observed previously: 33 in environmental samples taken from more remote locations downwind from the test site, the 135 Cs-rich "far-end" with samples exhibiting a high 135 Cs/ 137 Cs ratio. 33 Here, to the best of our knowledge, we observe for the first time the complementary 137 Cs-rich "near-end" showing the opposite pattern with a low 135 Cs/ 137 Cs signature.…”
Section: Cs Csmentioning
confidence: 73%
“…However, the 108 Pd/ 105 Pd ratio showed no difference from natural Pd within the measurement uncertainties. Note that shifts of the stable isotope through nuclear causes are rarely observed in environmental samples. , Thermal fission yields of both 235 U and 239 Pu favor the production of 105 Pd over 108 Pd. Hence, spent fuel at the end of its lifetime exhibits low values for the 108 Pd/ 105 Pd ratio, at least when compared to natural Pd.…”
Section: Resultsmentioning
confidence: 99%
“…Work by Byerly et al described how details of reactor conditions, including the flux, irradiation time, and cooling time, could be inferred through measurements of both cesium and ruthenium fission products in archived natural uranium targets from a light water-moderated research reactor (LWR). More recently, Hopp et al reported measurements of stable Ru in an environmental filter paper sample where 106 Ru was detected. The filter paper collection was part of a larger event where 106 Ru was detected across Europe during several months in the fall of 2017. , The stable Ru isotopic composition in the paper was consistent with release from spent fuel and comparison with select values reported for different reactor types pointed toward a water–water energetic reactor (VVER) as the source of the emissions .…”
Section: Introductionmentioning
confidence: 91%
“…More recently, Hopp et al reported measurements of stable Ru in an environmental filter paper sample where 106 Ru was detected. The filter paper collection was part of a larger event where 106 Ru was detected across Europe during several months in the fall of 2017. , The stable Ru isotopic composition in the paper was consistent with release from spent fuel and comparison with select values reported for different reactor types pointed toward a water–water energetic reactor (VVER) as the source of the emissions . This prior work suggested that 106 Ru measurements could have important future applications in environmental monitoring, as this volatile radioisotope (RuO 4 , boiling point: 40 °C) can be released in nuclear accidents and other nuclear activities. , …”
Section: Introductionmentioning
confidence: 91%